Success of dental implants in compromised patients - Attia, Sameh; Justus Liebig University Giessen (My University, 2021)
Dental implants play a vital role in the oral and dental rehabilitation of patients with complex medical needs. Contraindications to implants are decreasing over time as a result of modern evidence-based clinical protocols, enhanced implant materials, and improved procedural strategies, such as augmentation of small and large defects. The present work aimed to evaluate dental implants' success and survival in medically and dentally compromised patients. Sufficient quality and quantity of bone and soft tissue are the essential requirements for implant placement, and atrophy of this tissue requires augmentation. However, donor-site complications should not be neglected when assessing the risk prevalence. Therefore, this thesis also evaluated the donor-site complications of two methods of augmentation used for compromised patients. The current work demonstrated the limitations associated with the established implant success criteria, which can only be circumvented by designing a new success score that includes objective and subjective parameters. Nonetheless, such a score should be initially revised by experts in the appropriate clinical field to ensure its acceptance by the community, after which the score shall be evaluated for accuracy by examiners in different dental centers. The previous points should be addressed through the formation of consortia supported by national and international associations, such as the German Association of Implantology.
Erfolg dentaler Implantate bei kompromittierten Patienten
Keywords: dental implant; success rate; compromised patients; ddc:610